(3JNejS HGfJ SYGO dcYH Hf RgjQs - (3eLghds; (3cYH Hf RgjQ , CHh GdeZQH,J (B26 (3g` s
(3ChdgG (B:s
(3aEfi deG hbaJ Ydi GdbUjOI GdeTghQI HHGfJ SYGO dcYH Hf RgjQ Hf CHj Sdei Oei HSja Gdghi hGdgLQ eWdhd hYbO UHQi Yf GdCMHGH eMdhd hOeY Yjfi Yf GdEQLGa ehUhd HGfJ SYGO abdHi Gdjhe eJHhd s
(3BNQgG (B:s
(3GdUdGI Ydi GdeNJGQ SjOfG NjQfG OjfG heQTOfG hNjQ OGY dehdGfG hefLOfG hBdg GdeUWajf GdZQ JYbOfG eGMQcJ ahb CTLGQ YKGcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GfXQgG eY eLehYI ajgG ef TYQ Hf RgjQ CHj Sdei hTYQ WQaIs
(3fSNI KGdKI cGdSGHbI JeGekGs
(3JHUQI GdYfhGf (B:s
(3JNejS TYQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B226s
Keywords: (3GdCOHs